PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN (ENDURANCE) ATLET KARATE DOJO PRESTASI INDONESIA KARATE- DO (INKADO) KAB. SIAK - sinaga, Bandarudin Welman; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstark: The problem in this research is that when a race in the first round is still strong and fast, so that the first half of its performance is maximized, the endurance of the athlete decreases on arrival in the second round and his race performance drops, no more force appears when pedaling. If this condition is allowed to continue, it is difficult for the athlete to achieve maximum performance. The title of this study is "The effect of interval training on the endurance of the Indonesian Karate Dojo performance Karate-Do (INKADO) district. Siak" so that the future goals of athletes after research can perform much better and especially after research and discover whether there are an increase in endurance is for karate athletes to balance the game of the opponent and to achieve maximum results in the future. The form of this research is (with the help of a one-group pre-test design approach) with the population of the Indonesian Karate-Do Achievement Dojo Team (INKADO) Kab. Siak. The data in this research are the entire population of 10 people. The instrument used in this study was to use a beam test, which aimed to determine the effect of interval training on endurance in the Indonesian Karate Dojo Achievement Karate-Do (INKADO) Kab. Siak. The data is then statistically processed to test the normality with the help of the lilifours test at a significant level of 0.05?. The proposed hypothesis is that there is an influence of endurance training interval training on the Indonesian Karate Dojo Achievement Karate-Do (INKADO) district. Siak. Based on the analysis of the normality of the data X, it produces an Lcount of 0.164 and an Ltable of 0.258, which means that Lcount <Ltable. while the Y variable yields Lcount of 0.127 and Ltable of 0.254. This means Lcount <LTable. Based on statistical data analysis, there is an average variable X 39.46 and an average variable Y of 42.29, after which the data is normally distributed. Thus it can be concluded that for the effect of the variable x with the obtained variable y the value of t = 6,288 is then tcount> ttable (6,288)> (1,833), then Ha is accepted, in other words, there is a significant effect on the effect of interval training on endurance (Endurance) Indonesian Karate Dojo performance Karate-Do (INKADO) Kab. Siak.Key Words: Interval Training, Endurance